Land Use and Water Management in Israel- Economic and environmental analysis of sustainable reuse of wastewater in agriculture - Nava Haruvy (European Regional Science Association (ERSA), 2005)
We will analyze land use and water management issues in Israel by focusing on wastewater irrigation. Irrigation with treated effluents has become an important water source in Israel due to scarcity of natural water resources. Treated wastewater reuse serves as source of water and nutrients and assists with wastewater discard. Wastewater also carries pollutants including micro and macro organic and inorganic matter and its treatment and use should adapt to sustainability criteria. Wastewater treatment processes can decrease pollutants levels, while salinity is not influenced unless combining relatively expensive desalination processes. Advantages of using wastewater in irrigation include: supporting agricultural production, highly reliable supply, low cost water source, solution for effluent disposal and saving of chemical fertilizers. Disadvantages include quality problems as related to human health, damage to crops, contamination of groundwater, problems related to irrigation system, increased water requirement and need for continuous follow up and control. The higher is the treatment level, the higher are the treatment costs but the environmental potential hazards are lower. Regarding sustainable use we will assess advantages and disadvantages of treating and irrigating with treated effluents. We will focus on the economic and environmental analysis of sustainable reuse of wastewater in agriculture regarding its impact on groundwater, soil and society.
Keywords: 330